The Impact of Executive Attention Strategy on EFL Preparatory School Pupils’ Ideational Behaviour (Journal of the College of Education for Women, 2026)
Most of the pupils depend in their learning on memorization, repetition and modeling, they do not try to think out of the box. Greater significance has been given to improving pupils’ thinking skills because of all the rapid changes in the world. The objective of the current study is to examine how executive attention technique affects the ideational behavior of EFL preparatory school pupils for the 2024–2025 academic year. For this objective, the following hypothesis was formulated: “There is a significant impact of executive attention strategy on EFL preparatory school pupils’ ideational behavior”. To achieve this objective, Runco Ideational Behavior Scale is used. This scale is a five-point Likert scale questionnaire with 23 items based on Runco et al. (2001), ranging from 1(never) to 5 (always). The population in this research is all fourth preparatory in Al-Nahda Secondary School for Girls, where the total number is 250. The sample consisted of (74) pupils who were randomly chosen. The results showed that pupils' ideational behavior conduct post-test total score differed statistically significantly between the two research groups, favoring the experimental group that received instruction by using the executive attention strategy.